1993
DOI: 10.1016/0014-5793(93)81329-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of β2‐adrenergic receptor mRNA expression along the hamster nephron segments

Abstract: Distribution of 82-adrenergic receptor mRNA expression along the microdissected hamster nephron segments was examined by the reverse transcription-polymerase chain reaction (RT-PCR) technique. Conventional RT-PCR using a set of primers on separate exons could not be applied for the detection offi2-adrenergic receptor mRNA because of its intronless nature. We used the 'rapid amplification of cDNA ends' protocol [(1985) Proc. Natl. Acad. Sci. USA 85, 8998-90021 as a maneuver for RT-PCR of an intronless gene. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous reports (34,35) demonstrated that renal ␤ 2 -AR in normal rats were predominantly localized to the apical and sub-apical compartments of proximal and, to a lesser extent, distal tubular epithelia and the membranes of smooth muscle cells from renal arteries. From this morphologic evidence, it was proposed that ␤ 2 -AR may regulate glomerular function and thereby sodium and water balance in the different nephron segments.…”
Section: Discussionmentioning
confidence: 87%
“…Previous reports (34,35) demonstrated that renal ␤ 2 -AR in normal rats were predominantly localized to the apical and sub-apical compartments of proximal and, to a lesser extent, distal tubular epithelia and the membranes of smooth muscle cells from renal arteries. From this morphologic evidence, it was proposed that ␤ 2 -AR may regulate glomerular function and thereby sodium and water balance in the different nephron segments.…”
Section: Discussionmentioning
confidence: 87%
“…, 1994). Previous reports have demonstrated that renal β 2 ‐adrenergic receptors in normal rats were predominantly localized to the apical and sub‐apical compartments of proximal and, to a lesser extent, distal tubular epithelia and the membranes of smooth muscle cells from renal arteries (Taniguchi et al. , 1993; Boivin et al.…”
Section: Introductionmentioning
confidence: 99%